Applications of NMR Spectroscopy - Atta-ur-Rahman (Applications of NMR Spectroscopy Ser., 2020)
Applications of NMR Spectroscopy is a book series devoted to publishing the latest advances in the applications of nuclear magnetic resonance (NMR) spectroscopy in various fields of organic chemistry, biochemistry, health and agriculture. The eighth volume of the series features six reviews focusing on NMR spectroscopic techniques in food science, molecular biology and medical diagnosis. The reviews in this volume are: - qNMR as a Tool for Determination of Six Common Sugars in Foods - Correlation of VIP Scores and 1H NMR to Extract Information of Psychological Attention Tests Applied Before an.